What Explains the Quantity and Quality of Local Inventive Activity? - Carlino, Gerald; Hunt, Robert (Brookings-Wharton Papers on Urban Affairs, 2009)
The article examines the dimensions of the quantity and quality of local inventive activity in the U.S. It states that growth in knowledge of the population serves a catalyst in the economic growth of nations. An elaboration on the measures of quality inventions and trends in the local academic research and development field is also presented.